PRESENT-DAY CONDITION OF THE SYSKYÄNJOKI RIVER (LAKE LADOGA CATCHMENT, REPUBLIC OF KARELIA) - Sergey Komulaynen; Pyotr Lozovik; Alexandra Kruglova; Igor Baryshev; Yulia Slastina; Natalia Galibina (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2017)
The chemical features and the structure of biological communities in the Syskyänjoki River are considered. Comparative analysis was carried out for the species composition, abundance and biomass of phytoplankton, phytoperiphyton, zooplankton, and zoobenthos in the Syskyänjoki River based on observed data from August 2014. The effect of natural and anthropogenic factors on the formation of the chemical features and structure of the river's hydrobiocoenoses was analyzed. The trophic status of the river, its saprobiological state, and the significance of individual communities and biotic indices for bioindication of the ecological condition of the river were assessed. Particular attention is given to the effect of flowage lakes and urbanisation in the catchment. The dominant complex is represented by a moderate range of species resistant to dynamic water load. The abundance and biomass of phytoperiphyton, zooplankton, and zoobenthos point to a relatively high degree of their development in the river water, as well as their activity and stability. A peculiarity of the structure of the hydrobiocoenoses is that they consist of species with appreciably different sizes: from several microns to several centimeters. Therefore, the lists of species dominating in terms of abundance and biomass differ considerably. The work was done in connection with the plans to establish protected areas in the Syskyänjoki River basin.